Study on Flood Season Staging in Longtan Reservoir Based on Fisher Optimal Dissection Method - LI Dongqin; HUANG Ya; YI Ling; HOU Guibing; LI Yuanyuan (Renmin Zhujiang)
Based on the daily data of precipitation and runoff over the Longtan reservoir from 1960 to 2015,this paper selects four weight assignment methods to calculate the feature vector of flood season stages based on Fisher optimal dissection method,and analyzes the number of optimal flood season stages of the reservoir.The results show that:When ten days are used as the unit of flood season staging,the weight coefficients have little influence on the result of flood season staging.The flood season staging results of the Longtan reservoir based on the Fisher optimal dissection method can better reflect the characteristics of rainstorms and flood in the flood season of the basin,and the optimal number of flood season stages is five.According to the optimal staging results,the flood season in the Longtan reservoir is divided into pre-flood transition period (April 1~April 30),pre-flood period (May 1~May 20),main flood period (May 21~July 20),post-flood period (July 21~September 10) and post-flood transition period (September 11~October 31).